CONSUMERS' PERCEPTIONS OF FOOD SUSTAINABLE DESIGN PACKAGING: A SYSTEMATIC LITERATURE REVIEW - Alin-Ionuț HOSU; Alexandra-Ioana GLOGOVEȚAN; Cristina Bianca POCOL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Packaging plays an essential role in ensuring that goods are delivered safely and in good condition to the final consumer within supply chains. Packaging also has many potentials to help with the long-term development of food products. This review paper investigates consumer perceptions and understanding of design food packaging and how design packaging can help the environmental pillar of sustainable development. A literature analysis was conducted using the search strategy in Web of Science as well as other suitable international databases based on their global accessibility and researchers' library access. The result indicates that, from the consumer's standpoint, the essential aspect of sustainable packaging is represented by packing materials, and the packaging design must contain information about recycling actions. Considering the current issues, such as plastic waste and plastic packaging, the consumers believe that sustainable packaging is not as available on the food market as expected.